The physical and optical studies of erbium doped borosilicate glass - Razali, Nur Ain Nabilah; Mustafa, Iskandar Shahrim; Noor Azman, Nurul Zahirah; Mohamed Kamari, Halimah; Abd Rahman, Amalina; Rosli, Khairiah; Taib, Noor Syamimi; Tajuddin, Nur Adilah (IOP Publishing, 2018)
A glass series of erbium doped zinc borosilicate glass system was prepared by using the melt-quenching method. The absorption spectra revealed several bands at visible range which correspond to the following transitions (from the ground state); ⁴F5/2 + ⁴F7/2 + ²H11/2 + ⁴S3/2 + ⁴F9/2 + ⁴I9/2. The density and molar volume obtained increased and decreased respectively as the concentration of erbium oxide varied from 0 mol % to 1.0 mol %. Meanwhile, oxygen packing density (OPD) increased as the concentration of erbium oxide increased up to 3.0 mol % due to the build-up of bridging oxygen. The indirect band gap energy was achieved from 2.56 eV to 2.80 eV and the Urbach energy values lies between 0.15 eV and 0.61 eV.